Methimazole induced lichenoid eruptions: an unusual case - G. N., Vibhashree; H. V., Anuradha; Kalra, Pramila (International Journal of Basic & Clinical Pharmacology, 2017)
This is a case report of a 31-year-old male presented to the Endocrinology outpatient department of our hospital with hyperthyroidism and was prescribed tablet methimazole 30mg once daily and tablet propranolol 40mg once daily. After 3 months, the patient complained of violaceous papular lesions on both the extensor aspect of the arms and legs. Physical examination was remarkable for acute onset, raised, itchy, violaceous papular lesions over the defined areas. The drug methimazole was suspected to cause lichenoid drug eruptions and was withdrawn. This case illustrates methimazole otherwise an efficacious and widely used anti thyroid drug is an agent capable of inducing lichenoid eruptions. However in future the monitoring of methimazole is essential for such adverse reaction.